FORMULASI SEDIAAN KRIM ANTIOKSIDAN EKSTRAK METANOL KULIT BUAH PISANG RAJA (Musa paradisiaca L.) - Dwi Ayunda Putri; Endang Sri Rejeki; Siti Aisiyah (FKIP Universitas Tanjungpura, 2023)
Antioxidant compounds are compounds that counteract or reduce the negative impact of oxidants, which work by donating one electron charge so that the activity of these oxidant compounds can be prevented or inhibited. The aim of this study was to determine the formula for cream variation of extract from banana peel which has the best antioxidant activity with good quality and stability of the preparation. In this study, the antioxidant cream used 3 (three) series of concentrations of the methanol extract of the skin of the plantain (Musa paradisiaca L.) fruit, namely 0.5%, 1% and 2%. The methanol extract of plantain peel was obtained by maceration method with methanol as solvent. Antioxidant cream was tested for physical quality and stability which included organoleptic test, viscosity test, pH test, homogeneity test, adhesion test, and spreadability test. The antioxidant power test was carried out using the DPPH (1,1-Diphenyl-2-Picrylhydrazyl) method using a UV-Vis spectrophotometer with a wavelength of 400-600 nm. The results of the study were further analyzed statistically using the Tukey method and one-way ANOVA. The results showed that the methanol extract of plantain peel had very strong antioxidant activity, and cream preparations could be made with various extract concentrations and the IC50 values of formula 1, formula 2 and formula 3 were 53.81 ppm, 53.29 ppm and 53.21 ppm.